How changes in localized pressure under an experimental acrylic plate covering the palatal mucosa affect salivary cortisol concentration and α-amylase activity - Maeda, Teruta; Ito, Hidetaka; Okazaki, Joji (Journal of Osaka Dental University, 2009)
We quantified the degree of discomfort induced by plates of different thicknesses placed under an experimental acrylic plate (exp. plate) covering the palatal mucosa in an attempt to model ill-fitting dentures. Both salivary cortisol concentration and α-amylase activity were measured in response to the discomfort caused by varying localized pressure on the experimental acrylic plate. Nineteen healthy subjects with an average age of 25±2 years were included in this study. All subjects were seated and examined under the five experimental conditions of N (not wearing an exp. plate), D (wearing an exp. plate), DP 1 (wearing an exp. plate with a 0.1-mm-thick localized pressure plate), DP 2 (wearing an exp. plate with a 0.2-mm-thick localized pressure plate) and DP 3 (wearing an exp. plate with a 0.5-mm-thick localized pressure plate). Subjects were then asked to complete a Visual Analogue Scale (VAS) during each condition. Saliva samples were collected at 0, 5, 10, 15 and 20 min after the start of each condition. Cortisol concentration and α-amylase activity were measured using enzyme-linked immunosorbent assay and kinetic analysis. Salivary cortisol concentration and α-amylase activity significantly increased as the pain and discomfort resulting from localized pressure increased. Cortisol concentration and α-amylase activity for condition D were significantly greater than that for N. Although the pain score, as measured by VAS, was the same for conditions N and D, significant differences in discomfort were found between N and D. We concluded that the severity of palatal mucosa stimulation and discomfort may be objectively assessed using salivary cortisol concentration and α-amylase activity.